2017
DOI: 10.1037/vio0000060
|View full text |Cite
|
Sign up to set email alerts
|

Just a dare or unaware? Outcomes and motives of drugging (“drink spiking”) among students at three college campuses.

Abstract: Objective: Drugging (administering a drug to someone without their knowledge or consent) is acknowledged as a problem in "watch your drink" campaigns. However, research on this phenomenon is nascent. Prior research has primarily focused on drugging as a means of sexual assault, and has not addressed drugging more generally. Method: Survey data from 6,064 students at 3 universities was used to explore drugging among those who had drugged someone (or knew someone who had) and those who had been drugged. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
(41 reference statements)
1
21
0
1
Order By: Relevance
“…Coker et al (2016), in their survey of 959 American women aged 18–24, found that 7.8% of college women and 8.5% of noncollege women had experienced drugging victimization in their lifetimes. These rates were similar to those uncovered by Swan et al (2016) in their study of drugging among male and female students on three college campuses. They found that 7.8% ( n = 462) of their sample had experienced at least one incident of drugging victimization since the start of the academic year, accounting for a total of 539 separate drugging incidents.…”
Section: Drugging Victimization and The Campus Contextsupporting
confidence: 82%
See 3 more Smart Citations
“…Coker et al (2016), in their survey of 959 American women aged 18–24, found that 7.8% of college women and 8.5% of noncollege women had experienced drugging victimization in their lifetimes. These rates were similar to those uncovered by Swan et al (2016) in their study of drugging among male and female students on three college campuses. They found that 7.8% ( n = 462) of their sample had experienced at least one incident of drugging victimization since the start of the academic year, accounting for a total of 539 separate drugging incidents.…”
Section: Drugging Victimization and The Campus Contextsupporting
confidence: 82%
“…They found that 7.8% ( n = 462) of their sample had experienced at least one incident of drugging victimization since the start of the academic year, accounting for a total of 539 separate drugging incidents. Combining the three-campus data used by Swan et al (2016) with an additional year of data from one of the campuses, Lasky et al (2017) found that 6.16% of undergraduates had been drugged in the past academic year, with 20% experiencing more than one drugging victimization. There were a total of 574 separate drugging incidents, with recurring victims experiencing 42% of all drugging incidents.…”
Section: Drugging Victimization and The Campus Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu yanıtlar cinsiyetlere göre farklılaşmaktadır. MKCS olgusunun mağduru olmuş ya da bu olaya tanık olan kadınlar, faillerin cinsellik ya da cinsel saldırı amacıyla içeceklere madde karıştırdığını düşünürken erkekler faillerin eğlence amaçlı bu davranışı gerçekleştirdiğini öne sürmektedir (22).…”
Section: Failunclassified